Educating Effervescent Women Scientists through Lucy Maud Montgomery’s Anne of Green Gables - Seng, Tong Chong; Ng , Yu Jin; Karthikeyan, J; Mohd Kasim, Zalina; Lee , Su Yee (Journal of Techno-Social, 2021)
The series Anne of the Green Gables is sequential children books that focus on Anne Shirley, the story’s protagonist. The series of books explore Anne’s life from a girl to a charming pretty young lady. In the story, Anne is portrayed as an inquisitive young girl. She explores her life philosophically. She also explores many aspects of nature and its relation to science. Her inquisitiveness is extremely sharp, that the skill helps her in learning the science of everyday life. The paper discusses Anne of the Green Gables’ use in educating female students to enjoy STEM education. At present, the proportion of women engineers in Malaysia is disproportionate, and the Ministry of Education is working on inculcating female students’ effervescence in STEM subjects. The methodological framework utilised in this study adhered to the approach of the phenomenological case study’s paradigm. Interviews were conducted, and qualitative data were gathered and analysed using Atlas.ti, a qualitative data analysis software. The findings indicated that female students could draw links between themselves and Anne, the protagonist in the novels. The protagonist’s various occupational explorations helped female students understand that they can excel in STEM and arouse their interests to become scientists or engineers. In conclusion, the use of literary texts written by female authors such as Anne of Green Gables could draw attention from female students towards STEM. This study fills the gap in the existing literature where no scholars have used the classic Anne of Green Gables to illicit interests among young female students.